An Emerging Way for Bacteria to Engage with Host Cells via Protein ADP-riboxanation - Xian, Wei; Tang, Zhiheng; Zhang, Qinxin; Wang, Ying; Liu, Xiaoyun (Toxins, 2024)
Post-translational modifications (PTMs) are increasingly recognized as important strategies used by bacterial pathogens to modulate host cellular functions. Protein ADP-riboxanation, a derivative of ADP-ribosylation, has recently emerged as a new biochemical way by which bacterial pathogens interact with host cells. Recent studies have revealed that this modification has broad regulatory roles in host processes including cell death, protein translation, and stress granule formation. Given that the vast majority of bacterial ADP-riboxanases are still uncharacterized, in this review we also highlight the utility of advanced proteomic tools in the functional dissection of ADP-riboxanation events during bacterial infections.